High podoplanin and low E‐cadherin levels correlate with better prognosis in adenoid cystic carcinoma - Jacqueline E. van derWal; Nicola Sgaramella; Lena Norberg Spaak; Katarina Zborayova; Karin Nylander (Wiley, 2019)
Abstract Objectives As tumour spread is a complicating event for malignant salivary gland tumours, we decided to study factors related to cell adhesion and lymph vessel formation in two of the three most common malignant salivary gland tumours, mucoepidermoid carcinoma (MEC) and adenoid cystic carcinoma (ACC), to clarify the clinical relevance and potential usefulness of these factors. We also included a group of polymorphous adenocarcinoma (PAC) as this tumour, in common with ACC often shows perineural growth, but in contrast to ACC has an overall good prognosis. Material and methods Eighteen patients with ACC, 15 with MEC, and six with PAC were included. Protein expression of podoplanin and E‐cadherin was evaluated as percentage of cells expressing the protein and intensity of expression. Ki‐67 expression was included in the study as a marker of proliferative activity. Results Looking at podoplanin, significantly more ACCs were high expressing compared with both MECs (P = .001) and PACs (P = .028). Also when looking at Ki‐67 expression, significantly more ACCs were high expressing compared with MECs (P = .003). Significantly better survival was also seen for ACCs with high podoplanin (P = .022) and low E‐cadherin expression (P = .021), respectively. Conclusions Our findings show that ACCs express significantly higher levels of podoplanin compared with both MECs and PACs and that high levels are correlated to better survival. Even though the group of PACs analysed was small, these tumours, despite their tendency to perineural spread, which they have in common with ACC, differ from ACCs concerning expression of factors with a known connection to tumour spread.